2019
DOI: 10.1093/biolre/ioz160
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia–telangiectasia mutated coordinates the ovarian DNA repair and atresia-initiating response to phosphoramide mustard

Abstract: Ataxia–telangiectasia-mutated (ATM) protein recognizes and repairs DNA double strand breaks through activation of cell cycle checkpoints and DNA repair proteins. Atm gene mutations increase female reproductive cancer risk. Phosphoramide mustard (PM) induces ovarian DNA damage and destroys primordial follicles, and pharmacological ATM inhibition prevents PM-induced follicular depletion. Wild-type (WT) C57BL/6 or Atm+/− mice were dosed once intraperitoneally with sesame oil (95%) or PM (25 mg/kg) in the proestru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 119 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…It is known that DDR molecules downstream of ATM are blunted due to DMBA exposure in obese mice, albeit in older mice [ 22 ]. It is also known that both ATM inhibition [ 67 ] and Atm haploinsufficiency [ 24 ] impair depletion of damaged ovarian follicles. Thus, this lack of primary follicle depletion by DMBA could support a defective ovarian DDR response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that DDR molecules downstream of ATM are blunted due to DMBA exposure in obese mice, albeit in older mice [ 22 ]. It is also known that both ATM inhibition [ 67 ] and Atm haploinsufficiency [ 24 ] impair depletion of damaged ovarian follicles. Thus, this lack of primary follicle depletion by DMBA could support a defective ovarian DDR response.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of the intensity of the BRCA1 stain in oocytes revealed a decrease in BRCA1 in the oocytes of primary follicles in all treatment groups as compared with lean control. Previously our group has reported a decrease in BRCA1 abundance with progressive obesity [ 22 ] and in 10-week-old mice no observable changes in BRCA1 were noted suggesting that the alterations in BRCA1 previously noted could be age-related [ 24 ]. Herein decreased BRCA1 in the oocytes of primary follicles due to both DMBA and obesity exposure was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ataxia telangiectasia mutated (ATM) could be activated in response to DNA damage, which lead to phosphorylation of downstream proteins to regulate apoptosis and cell cycle in cancer (12). It was reported that loss of ATM prolonged the diestrus phase in mice, ATM inhibition suppressed phosphoramide mustard induced destroys primordial follicles (13). However, the exact mechanism underlying tumor growth inhibition induced by ATM blockage were still unclear.…”
Section: Discussionmentioning
confidence: 99%